2019
DOI: 10.4067/s0034-98872019000500628
|View full text |Cite
|
Sign up to set email alerts
|

Efectos en la función renal de la suplementación de creatina con fines deportivos

Abstract: Effects of creatine supplementation on renal function Creatine supplements may transitorily rise serum creatinine levels and mimic a kidney disease. If its use is associated with a high protein diet, the resulting increase in blood urea nitrogen will increase the confusion. Since clinical laboratories usually inform the estimated glomerular filtration rate based on serum creatinine, its elevation may lead to over diagnose a chronic renal failure, with the inherent personal and public health consequences. Creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
5
0
3
Order By: Relevance
“…Biochemical test results showed that cisplatin could signi cantly reduce renal function in rats. Blood creatinine and urea nitrogen levels can re ect the ltration function of the kidney [57][58], which can intuitively re ect the function of the kidney. Serum creatinine and urea nitrogen levels were signi cantly increased in model group compared with control group.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical test results showed that cisplatin could signi cantly reduce renal function in rats. Blood creatinine and urea nitrogen levels can re ect the ltration function of the kidney [57][58], which can intuitively re ect the function of the kidney. Serum creatinine and urea nitrogen levels were signi cantly increased in model group compared with control group.…”
Section: Discussionmentioning
confidence: 99%
“…Odżywki kreatynowe są często stosowane przez osoby regularnie ćwiczące, kulturystów i sportowców zawodowych jako substancja ergogeniczna. Jej stosowanie jest akceptowane jako legalny produkt przez światową agencję antydopingową [2].Jest jednym z suplementów diety, które zostały poddane dokładnym analizom. Istnieje kilka form kreatyny.…”
Section: Wprowadzenieunclassified
“…u sportowców wysiłkowych trenujących nie krócej niż rok i z wysokim spożyciem białka (1,2-3,1 g/kg/dzień), którym podawano suplementy kreatyny w dawkach obciążeniowych i podtrzymujących lub placebo, nie wykazały zmian w stężeniach mocznika i kreatyniny w surowicy ani w szybkości filtracji kłębuszkowej. Doszli do wniosku, że suplementy diety są bezpieczne i nie wpływają na czynność nerek[2,8].W ciągu ostatnich kilku lat badania wykazały, że przyjmowanie preparatów zawierających kreatynę może zmniejszyć gromadzenie się tłuszczu w wątrobie, a także zahamować progresję niealkoholowego stłuszczenia wątroby. Pierwsze dowody na ochronne działanie suplementacji kreatyny przeciwko stłuszczeniowej chorobie wątroby zostały przedstawione przez Demince i wsp.(2011).…”
unclassified
“…El metabolismo de la creatinina y su excreción extrarrenal son menores en sujetos mayores, salvo en aquellos que tienen una función renal reducida 8,10 . Cantidades significativas de creatinina se eliminan por las heces y una parte de ella es degradada en el tubo digestivo 15 . En la insuficiencia renal crónica aumenta el clearance extrarrenal de creatinina y la excreción de creatinina por orina disminuye en hasta un tercio de la de un sujeto normal en pacientes con insuficiencia renal crónica avanzada 8 .…”
Section: Factores Que Influyen En La Excreción De Creatinina En Orinaunclassified